(Ns(B. (Nm(B. (NlQPUNOW (B:s (NO^ERK VIZNI I TWOR^ESTWA (B/s - (N{IFMAN(B, (NmIHAIL eFIMOWI^(B,s; (NsOKOLOWA(B, (Nt(B.,s ((NmOSKWA (B:s (NmUZGIZ(B,s, 1960)
(No MNOGOSTORONNEJ DEQTELXNOSTI s(B. (Nm(B. (NlQPUNOWA (B- (NKRUPNOGO KOMPOZITORA(B, (NMUZYKOWEDA(B, (NDIRIVERA I PIANISTA(B.s
(NsPISOK SO^INEN(B.: (NS(B. 138-142s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NlQPUNOW s(B. (Nm(B.s; )Qæ(NSTORÆQ MUZIKIs)E -- (NkOMPOZITORIs; (NB)QÆOGRAFÆQs)E; (NNARISIs; (NP)QÆANÆZMs)E; (NROS)QÆJSXKÆ KOMPOZITORIs)E; (NSIMFON)QÆQs)E; (NTWOR^)QÆSTX KOMPOZITORÆWs)E; (NET@DI DLQ FORTEP)QÆANOs)E